Analysis of umami taste substances of morel mushroom (Morchella sextelata) hydrolysates derived from different enzymatic systems. (15th November 2021) - Gao, Juan; Fang, Donglu; Muinde Kimatu, Benard; Chen, Xin; Wu, Xian; Du, Jiaxin; Yang, Qian; Chen, Hui; Zheng, Huihua; An, Xinxin; Zhao, Liyan; Hu, Qiuhui
Highlights: Defective fruiting body waste of morel mushroom was used to extract taste compounds. The Neutrase-Flavourzyme combination (NF) yielded most umami taste contributors. Peptides of 1–3 kDa contributed more to umami and saltiness of hydrolysates from NF. The highest degree of hydrolysis of NF after optimization by RSM was up to 36.64%. Morel hydrolysates obtained from NF would be a high-quality flavoring agent. Abstract: Seven enzyme groups were applied to hydrolyze broken fruiting bodies of morel mushroom ( Morchella sextelata ) to extract umami substances. Physical-chemical properties, as well as compositions and concentrations of quintessential umami compounds of morel hydrolysates were analyzed. Electronic tongue and electronic nose were used to evaluate the sensory characteristics. The results suggested that peptides below 3 kDa showed the highest correlation with umami taste. Morel hydrolysate obtained from Neutrase-Flavourzyme (NF) combination contained the most contents of small peptides (<3 kDa), free amino acids (224.83 ± 0.87 mg/g), as well as flavor 5′-nucleotides (4.84 ± 0.32 mg/g), giving the best overall flavor properties. The reaction conditions of NF were optimized by response surface methodology (RSM). The highest degree of hydrolysis (DH) was up to 36.64%. An enzymatic hydrolysis approach was established to develop novel flavor products with high umami and low bitter taste from morel mushroom.